International migration in the context of financial and economic security: The role of public administration in the development of national economy, education, and human capital - Pavlovskyi, Oleh; Blikhar, Mariia; Akimova Liudmуla; Kotsur, Vitalii; Akimov, Oleksandr; Karpa, Marta (Edelweiss Applied Science and Technology, 2024)
The article outlines trends in today global migration and its consequences for economic growth and security. Both positive and negative sides of ongoing processes are analyzed, in particular the effect of remittances on the one side and money laundering and terrorism financing due to activities of criminal organizations involved in migrant smuggling on the other side. Accordingly, challenges and goals for national public administrations are indicted.